Randomised single centre double-blind placebo controlled phase II trial of Tocovid SupraBio in combination with pentoxifylline in patients suffering long-term gastrointestinal adverse effects of radiotherapy for pelvic cancer: The PPALM study. (March 2022) - Andreyev, H. Jervoise N.; Matthews, Jennifer; Adams, Carolyn; Gothard, Lone; Lucy, Claire; Tovey, Holly; Boyle, Sue; Anbalagan, Selvakumar; Musallam, Annette; Yarnold, John; Abraham, David; Bliss, Judith; et al.
Highlights: First human trial of gamma-tocotrienol with pentoxifylline assessing its potential to reduce radiotherapy-induced gastrointestinal damage . Change in bio-markers of fibrosis was also assessed. Compliance with prescribed study medication was excellent and treatment was well tolerated. Absorption of tocotrienol was inadequate in almost half the participants and this may explain previous contradictory results in Vitamin E analogue trials . Levels of cytokines which drive fibrosis were significantly reduced Consistent trends in reduced inflammation were seen during treatment but not sustained once treatment ended. Earlier treatment, in higher doses and continued for more than one year may be more effective. Abstract: Background: Preclinical data suggest that combined gamma-tocotrienol with pentoxifylline ameliorates radiotherapy-induced gastrointestinal damage. Aim: To test whether gastrointestinal symptoms arising after radiotherapy, and persisting after maximal medical therapy, can be improved using Tocovid SupraBio 200 mg and pentoxifylline 400 mg orally twice daily for one year. Patients stratified by severity of symptoms, and randomised to active treatment or matched placebo were assessed after 12 months. The primary end point was improvement in gastrointestinal symptoms measured using the Inflammatory Bowel Disease Questionnaire, bowel subset score. Changes in bio-markers of fibrosis were assessed. Results: 62 patients, median age 66, 34(55%) treated for prostate, 21(34%) gynaecological, 6(10%) anal and one(1%) rectal cancer were recruited; 40(65%) randomised to treatment, 22(35%) to placebo, 39 months (median) after radiotherapy completion. Gamma tocotrienol was not detected in serum in 41% of treated patients, despite good compliance with study medication. Treatment was completed in 28(70%) and 17(77%) patients in the treatment and placebo groups respectively. No improvement in symptom scores nor in quality of life was identified. Thirteen serious adverse events occurred. A transient ischaemic attack, was possibly related to pentoxifylline, others were assessed as unlikely to be related to treatment. Levels of EGF, PDGF and FGF were significantly reduced and consistent trends in reduced inflammation were seen during treatment but were not sustained once treatment ended. Summary: This single centre study closed prematurely and therefore data interpretation is of necessity limited. No clinical benefit was demonstrated. However, biochemical data suggest that this intervention does have anti-inflammatory and anti-fibrotic effects.